Examining the Role of Biology Teachers' Beliefs, Motivations, and Self-Reported Practices in Constructing Curves for Biology Class - Alhassan, Najmuddeen; Alhassan, Amina; Chioma, Akazi Frances (Indonesian Journal of Teaching in Science, 2024)
The present research pertains to the examination of educational beliefs, motivations, and self-reported practices of biology teachers. The study adopted descriptive research of the survey type to senior secondary school students in Kaduna South local government Nigeria and 42 teachers in the sampled schools. The primary objective of this study is to establish whether all local teachers hold identical views regarding curve constructions, are stimulated by curves, and possess the skill set to create curves. The results of the research revealed a significant correlation between teachers' beliefs and curve construction in biology science. Furthermore, the study discovered a significant association between teachers' self-reported practices and the curve construction they used in biology class. Given the evidence, instructors adopt a more affirmative approach. Biology teachers with high ability in curve construction have positively reported great achievement levels in teaching biology with relevant curve illustrations and their self-reported practices, helping students gain mastery of biology. Biology teachers should increase their cultivated positive thinking toward curve construction and devise means by which they can improve the use of curves when teaching students in the classroom. Teachers of biology should always be motivated by the government, school administrators, and society at large. Thus, they can improve their teaching ability and skill.